Dataset on contaminated steel/rubber contact: Effect of surface texture on friction coefficientzenodo - Bilel Jebali; Manuela Gennesseaux; Malal Kane (Data in Brief)
This data article presents an experimental dataset on the friction behaviour of steel/rubber contact under contaminated conditions, obtained using a pin-on-disc tribometer. The dataset includes time-resolved coefficient of friction (CoF) values recorded over 420 seconds per test for four steel samples with distinct surface textures (shot-peened and grooved). During testing, the disc rotated at a constant speed of 60 rpm. Three contamination protocols were applied: single wetting, periodic wetting, and grease application with periodic wetting. Additionally, the dataset provides detailed surface texture parameters derived from 3D surface mapping, and calculated following ISO 25178 standards. These data can be used to analyse the influence of surface texture on frictional behaviour under degraded contact conditions, validate numerical friction models, and support the development of engineered surfaces for optimized tyre-rail interactions. The dataset is available in CSV format and can be accessed using any text editor or data analysis software. This data article is related to the research article “Tyre/Rail Contact: An Experimental Investigation on Contaminated Contact Cases”, where the full experimental methodology is described.